Applying Foresight For Enhanced Climate Resilience and Agriculture Policy Development in the SADC Region - Chevallier, Romy; Benkenstein, Alex; Chesterman, Sabrina; Thornton, Philip K.; Neely, Constance (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
In the face of change, complexity and global interdependence, foresight, as a set of methods and approaches for future planning, provides a perspective and a set of tools that can help SADC member states build effective governance systems and policy responses to enhance climate-resilient agricultural development in the region. While it is impossible to predict the future, foresight offers policy makers approaches to ‘future-proof’ strategies aimed at enhancing planning, coordination, and solution design. This involves exploring and preparing for a diversity of possible scenarios, identifying new opportunities and key challenges, and designing innovative and participatory ways of responding to challenges under rapidly evolving circumstances. Policy makers within SADC, and its 16 member states, can benefit from the development of plausible climateresilient pathways and multiple scenarios that consider tr ends, drivers, trade-offs and high-impact uncertainties. In a region that is already experiencing climate change-related warming, shifting rainfall patterns and other impacts, it is necessary to consider support structures and actions that can address future climate challenges, thereby building more climate resilient agricultural systems. The very nature of a globalised food production and consumption systems make food security vulnerable to events beyond the control of national governments, underscoring the importance of regional and global cooperation in responding to climate change-related threats to food security. Foresight can help gear the region’s policies to address longer-term, existential threats and assist governments to move away from reactive and crisis-management behaviours. These anticipatory practices can help SADC and its member states manage and plan for future risks and, ultimately, better protect vulnerable people and their livelihoods. To a certain extent, foresight has already been applied to planning and policy development in the region. However, there is further opportunity for governments to systematically incorporate foresight into national development visions and plans, anticipatory governance and strategic management, and policy and public services innovation to contribute to the realisation of African Union Agenda 2063, the UN Sustainable Development Agenda 2030 and the SADC Vision 2050.